Prognostic value of plasma diquat concentration in patients with acute oral diquat poisoning: a retrospective study - Meng, Na; Sun, Yiqing; Dong, Yanling; Lv, Baopu; Yao, Dongqi; Gao, Hengbo; Ma, Yu; Jin, Yingli; Zhu, Tieying; Tian, Yingping (Frontiers in Public Health, 2024)
Objectives: Diquat poisoning is an important public health and social security agency. This study aimed to develop a prognostic model and evaluate the prognostic value of plasma diquat concentration in patients with acute oral diquat poisoning, focusing on how its impact changes over time after poisoning.Methods: This was a retrospective cohort study using electronic healthcare reports from the Second Hospital of Hebei Medical University. The study sample included 80 patients with acute oral Diquat poisoning who were admitted to the hospital between January 2019 and May 2022. Time-to-event analyses were performed to assess the risk of all-cause mortality (30 days and 90 days), controlling for demographics, comorbidities, vital signs, and other laboratory measurements. The prognostic value of plasma DQ concentration on admission was assessed by computing the area under a timedependent receiver operating characteristic curve (ROC).Results: Among the 80 patients, 29 (36.25%) patients died, and 51 (63.75%) patients survived in the hospital. Non-survivors had a median survival time (IQR) of 1.3(1.0) days and the longest survival time of 4.5 days after DQ poisoning. Compared with non-survivors, survivors had significantly lower amounts of ingestion, plasma DQ concentration on admission, lungs injury within 24 hours after admission, liver injury within 24 hours after admission, kidney injury within 24 hours after admission, and CNS injury within 36 hours after admission, higher APACHE II score and PSS within 24 hours after admission (all P<0.05). Plasma Diquat concentration at admission (HR= Exp (0.032-0.059×ln(t))) and PSS within 24 hours after admission (HR: 4.470, 95%CI: 1.604~12.452, P=0.004) were independent prognostic factors in the time-dependent Cox regression model.Plasma DQ concentration at admission and PSS within 24 h after admission are independent prognostic factors for the in-hospital case fatality rate in patients with acute oral DQ poisoning. The prognostic value of plasma DQ concentration decreased with time.